Pathological and Cytological Studies on Hepatocellular Carcinoma in Cattle Slaughtered at Bishoftu Elfora Abattoir, Central Ethiopia - Mesfin Mathewos (Veterinary Medicine International)
Hepatocellular carcinoma (HCC) is one of the most common neoplasms that has been described in many domestic animal species. Hence, the disease has significant economic importance; thus, this study aimed to describe the cytopathological characteristics of hepatocellular carcinomas in cattle slaughtered at Bishoftu Elfora Abattoir, Central Ethiopia. A cross-sectional study design with a purposive sampling technique was performed from October 2017 to May 2018 using macroscopic, histopathologic, and cytological methods. For that matter, a total of sixty cattle were assessed for the presence of a hepatic tumor; however, only 1/60 (0.6%) case was found to be affected by hepatocellular carcinomas. On gross examination, hepatocellular carcinomas exhibited soft, white, multifocal nodules (10–40 mm in diameter) on different lobes of the liver. On the cut surface, the tumor revealed a sharply circumscribed border and was divided into lobules by thin connective tissue. The central zone of the tumors exhibited depression with a whitish fibrous area. Moreover, on histopathology, the tumors divulged unencapsulated carcinomatous lesions consisting of a thick, compact, somewhat ambiguous trabecular pattern of arrangement that was unglued by thin collagenous stroma. Cytological studies suggest that the tumor cells showed anisocytosis, anisokaryosis, prominent nucleoli, multinuclearity, palisading arrangements of neoplastic cells, increased N : C ratios, light eosinophilic cytoplasm, high mitotic index, and cytoplasmic and intranuclear vacuoles. In conclusion, cytopathological findings support a diagnosis of HCC in the liver; thus, further studies with a large sample size and use of immunohistochemistry are important for further characterization of hepatocellular carcinomas in cattle.